Home Environment and the Elderly: Objects and Products in Relation to the Physical Factors and Their Incidence on Early Dependence - Araya-Marchant, J; Araya-Leon, M (Springer Verlag, 2019)
The aging of population at the world level requires more research from different areas, with ergonomics playing an important role due to its multidisciplinary character. The relation of older adults with their objectual surroundings is specific and marginal in the representation of design. This hinders the basic activities of daily living (ADL) in the home environment. Their physical and cognitive specificities make us ask about and reflect on the factors that interfere with their performance and affect their autonomy, requiring us to promote an inclusive design for older persons. Because of the above, we value the need to prevent the deterioration of older persons and in this way favor their quality of life and autonomy. Furthermore, it is relevant that the dependence of older persons has a high individual and collective cost that affects a country’s welfare. Chile is projected for the year 2025 as the region’s most aged country, with around 25% of the people considered as older persons, and a progressive increase of dependent older persons who are added to the structural inequality, so we have a growing older population associated with impoverishment and femininity. Social services approach incipiently this situation, which from the health perspective, the dependence of older persons becomes a sanitary priority. The present proposal is framed in the first phase of the institutional project of the Universidad de Santiago de Chile, which is aimed at relating the physical (postures and movements) and the cognitive (perception) characteristics of older adults and the transition to dependence, in the ADL. The scientific development of the issue was examined through an INTEGRATIVE REVISION that answered the question: Which are the risk factors in daily life and its objectual environment, which attempt against the posture, anthropometry, and biomechanics of older adult men and women, that have an influence on mild dependence? Two search engines, PUBMED and WOS, were used, and among the results, it is highlighted that physical space must adjust to adapt to the physical, cognitive, and emotional changes caused by natural aging. On the other hand, in various studies it is seen that illumination, the ease of maintaining hygiene, and inappropriate furniture, are constant problems in houses, and this turns more serious with the risk of decreasing memory, among other. © Springer Nature Switzerland AG 2019.